THE DESIRABLE CHARACTERISTICS OF ADMINISTRATORS OF CHILD DEVELOPMENT CENTERS UNDER LOCAL ADMINISTRATIVE ORGANIZATIONS IN ANGTHONG PROVINCE - Kotkampa , Weena; Chaowarakul, Jitiyaporn; Mecharoen, Salinee (Journal of Educational Review Faculty of Education in MCU, 2024)
The purposes of this research is a mixed method. The research objectives were to: 1)The desirable characteristics of administrators of child development centers under local administrative organization in Angthong province, 2)Compare the desirable characteristics of administrators of child development centers under the local administrative organization in Angthong province, classified by age, education level, position and work experience and 3) The guidelines for developing the characteristics of administrators of the child development centers under the local administrative organization in Angthong province. The research is divided into 2 parts. Part 1 is quantitative research. The research samples were 200 teachers and educational personnel. The instrument for data collection was a set of questionnaires and the statistics for data analysis were mean, standard deviation, t–test (Independent Samples), and F–test (One –way ANOVA). Part 2 is qualitative research. The research samples were 5 educational institution administrators. The instrument for data collection was a set of structured interviews, and data analysis used content analysis. The results of the research showed that: 1) The desirable characteristics of administrators of the child development centers under local administrative organization in Angthong province, as a whole, were at a very high level. 2) A comparison of desirable characteristics of child development center administrators according to the opinions of teachers and educational personnel classified by education level, and position found no difference but age, work experience were different at a statistical significance of the 0.05 level. 3) Guidelines for developing desirable characteristics of executives This includes building good relationships with others, applying theory leads to appropriate practice, modeling good behavior Management based on the principles of good governance and communication development.